Glucose homeostasis in rats treated with 4-vinylcyclohexene diepoxide is not worsened by dexamethasone treatment. Issue 165 (January 2017) - Battiston, Francielle Garghetti; dos Santos, Cristiane; Barbosa, Amanda Marreiro; Sehnem, Sibele; Leonel, Ellen Cristina Rivas; Taboga, Sebastião Roberto; Anselmo-Franci, Janete A.; Lima, Fernanda Barbosa; Rafacho, Alex
Graphical abstract: Highlights: 4-VCD administered early in life causes ovary hypofunction in adult rats. GC side effects on glucose metabolism are not aggravated by ovarian failure in rats. Ovarian failure is not the sole factor mediating metabolic disturbances during aging. Abstract: 4-vinilcyclohexene diepoxide (4-VCD) causes premature ovarian failure and may result in estrogen deficiency, characterizing the transition to estropause in rodents (equivalent to menopause in women). Estropause/menopause is associated with metabolic derangements such as glucose intolerance and insulin resistance. Glucocorticoids (GCs) are known to exert diabetogenic effects. Thus, we aimed to investigate whether rats with premature ovarian failure are more prone to the diabetogenic effects of GC. For this, immature female rats received daily injections of 4-VCD [160 mg/kg body weight ( b.w. ), intraperitoneally ( i.p. )] for 15 consecutive days, whereas control rats received vehicle. After 168 days of the completion of 4-VCD administration, rats were divided into 4 groups: CTL—received daily injections of saline (1 mL/kg, b.w., i.p. ) for 5 days; DEX—received daily injections of dexamethasone (1 mg/kg, b.w ., i.p. ) for 5 days; VCD—treated as CTL group; VCD + DEX—treated as DEX group. Experiments and euthanasia occurred one day after the last dexamethasone injection. 4-VCD-treated rats exhibited ovary hypotrophy and reduced number of preantral follicles ( p < 0.05). Premature ovarian failure had no impact on the body weight gain or food intake, but both were reduced by the effects of dexamethasone. The increase in blood glucose, plasma insulin and triacylglycerol levels as well as the reduction in insulin sensitivity caused by dexamethasone treatment was not exacerbated in the VCD + DEX group of rats. Premature ovarian failure did change neither the hepatic content of glycogen and triacylglycerol nor the glycerol release from perigonadal adipose tissue. Glucose intolerance was observed in the VCD group after an ipGTT ( p < 0.05), but not after an oral glucose challenge. Glucose intolerance and compensatory pancreatic β-cell mass caused by GC were not modified by ovarian failure in the VCD + DEX group. We conclude that reduced ovarian function has no major implications on the diabetogenic effects promoted by GC treatment, indicating that other factors related to aging may make rats more vulnerable to GC side effects on glucose metabolism.